(untitled) (Research, Society and Development, 2020)
Tooth loss is a public health problem that affects millions of people. In this perspective, oral rehabilitation through implantology is an alternative, however, for this treatment to be possible, factors such as influences of systemic diseases and medications used by the patient need to be carefully checked. In this context, a group of drugs widely used are bisphosphonates (BFs), such drugs, widely used to inhibit bone resorption and treatment of malignant neoplasms directly influence the bone formation process. Thus, it is necessary to know the dental surgeon about the effects that such a group of drugs can measure the success rate of dental implants. The aim of the present study was to analyze the influence of the use of BFs in the process of osteointegration of dental implants. A literature review was carried out based on articles found on the platforms: Pubmed / Medline, Lilacs, SciELO and capes journals, from which 31 articles were selected due to their relevance to the topic. Therapy using BFs has proven safe in the literature as long as patients are not subjected to high doses of the drug, as well as do not use it in the intravenous form of administration. The success rate of dental implants proved to be equivalent to patients without treatment, however, we must pay attention to factors such as systemic diseases and deleterious habits that make the dental implant have failure rates regardless of the use of the drugs studied here.